The Assessment Process in Teaching and Learning English in the Midst of Covid-19 Pandemic - Werdiyanti, Ni Nyoman Diah (The Art of Teaching English as a Foreign Language (TATEFL), 2021)
The spread of Corona Virus Disease (COVID-19) made changes in education sector. The teaching and learning process change from blended learning into fully online learning. All the instructions are conducted fully online even the assessment, the important role in teaching and learning process, both the formative and summative assessment. The design of this study was Basic Interpretative Study. This study aimed to investigate the methods used by teachers in conducting the assessment as well as the challenges in doing assessment in fully online learning situation. High School English teachers were chosen to be the subject of this study. The results showed that teachers used E-portfolios, Self-assessment, and teachers’ feedback as the formative assessment and daily test, mid-terms test, final test in the forms of multiple choice, short answer, and essays, and final project as the summative assessment. However, teachers also found some difficulties in doing assessment in today’s online learning. Thus, the authorized government and other stakeholders are expected to hold seminar(s) or training(s) for teachers and provide appropriate services. Moreover, teachers are expected to enrich their assessment and digital literacy by joining seminar(s), webinar(s), or training(s).